PERANAN CITRA MEREK DAN PROMOSI DALAM MENINGKATKAN VOLUME PENJUALAN PADA AGEN PROPERTI FELIZ REALTY TANGERANG - Damayati, Erika Putri Damayanti; Hulasoh, Ela Hulasoh (Jurnal Media Komunikasi, 2025)
Brand image and promotion are two important factors as an attraction and advantage to win competition in the property sector amidst the proliferation of property agents. Building a brand image in the minds of consumers is not an easy thing, as is promotion which is one of the powerful weapons for companies in developing and maintaining business, because promotional activities require the right media so that the promotion carried out can be accepted by the public and get a good response. This research aims to determine the role of brand image and the role of promotion in increasing the sales volume of Feliz Realty property agents. This research uses a descriptive qualitative research approach, the unit of analysis is Feliz Realty which is located at Scintia Boulevard Ruko Darwin Timur No.58 Summarecon Gading Serpong, Pagedangan, Tangerang. The author acts as a research instrument. The data collection techniques are interviews, observation and documentation as well as literature study. The data analysis technique is data reduction, data presentation, conclusion drawing, then source triangulation. The results of this research state that, to build a brand image, property agent Feliz Realty introduces Feliz Realty to consumers using a digitalization system, carries out personal branding, participates in various events, and becomes a member of the Indonesian Real Estate Broker Association (AREBI), in order to introduce it well. horizontally to fellow companies in the property sector and verticals such as developers, also maintaining the quality of service to consumers through a one stop service system, so that it received an award as best supporting agent in 2022 held by the Sinar Gading Group. In terms of promotion, advertise on the portal rumah123.com, lamudi.com and rumah.com, various social media, various print media (banners, banners, brochures, billboards. Maximizing personal selling activities by collaborating with partners, websites, giving gifts like this is called with gimmicks and issued according to certain events or seasons from each developer, such as free Smart door lock, water heater, 20 million cashback, CCTV and free canopy, 0% down payment, 15 million cashback, giving away air conditioning, free name transfer financing, E-money amounting to 500 thousand, longer down payment installments, Ikea voucher of 5 million.